Cultural sustainability of African Canadian heritage: Engaging students in learning, the past, the present and the future. (July 2015) - Finlayson, Maureen
The focus of this research is cultural sustainability of African Canadian heritage. Research literature informs us that engaging youth in educational programmes at the local level is fundamental to sustainability discussions. Furthermore, students must be actively engaged in their African Canadian past, present and future education. However, there has been a lack of curricula and resources of African Canadian heritage in programmes, resulting in African Canadian students being unaware of the history, culture and positive contributions of their leaders to society. Educators of African heritage in Nova Scotia have developed African Canadian Studies 11. The interview data from African Canadian educators and students reveal the process for the development and implementation of this curriculum, the challenges that African Canadian educators face and the ways in which students become actively engaged in learning. The author suggests that this research has implications for cultural sustainability at the local and community level.